2017
DOI: 10.3791/55939
|View full text |Cite
|
Sign up to set email alerts
|

A <em>Caenorhabditis elegans</em> Nutritional-status Based Copper Aversion Assay

Abstract: To ensure survival, organisms must be capable of avoiding unfavorable habitats while ensuring a consistent food source. Caenorhabditis elegans alter their locomotory patterns upon detection of diverse environmental stimuli and can modulate their suite of behavioral responses in response to starvation conditions. Nematodes typically exhibit a decreased aversive response when removed from a food source for over 30 min. Observation of behavioral changes in response to a changing nutritional status can provide ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…Collectively, these data suggest that multiple food-associated volatile attractants can promote repellent barrier crossing in food-deprived animals. Consistently, a previous study showed that food-deprived animals are more likely to cross the repellent barrier when paired with a bacterial lawn [ 31 ]. To test whether food-deprivation differentially affected copper or diacetyl responses, we analyzed responses of these animals to varying concentrations of copper or diacetyl alone.…”
Section: Resultssupporting
confidence: 82%
“…Collectively, these data suggest that multiple food-associated volatile attractants can promote repellent barrier crossing in food-deprived animals. Consistently, a previous study showed that food-deprived animals are more likely to cross the repellent barrier when paired with a bacterial lawn [ 31 ]. To test whether food-deprivation differentially affected copper or diacetyl responses, we analyzed responses of these animals to varying concentrations of copper or diacetyl alone.…”
Section: Resultssupporting
confidence: 82%
“…Starved adults: Young adults were washed in a watch glass as described above, and then starved on a 10 cm 2% NGM plate without bacterial food for 3 h as previously described . Animals were placed within an annular ring of filter paper soaked in 20 mM copper chloride (CuCl 2 ) solution to keep them from crawling off the edges of plates, since copper is aversive to C. elegans (Campbell et al 2017). After 3 h of starvation, the CuCl 2 ring was removed, and the animals were collected from the plate and washed twice in M9 and once in ddH 2 O in a watch glass.…”
Section: Preparation Of Animals For Co 2 Chemotaxis Assaysmentioning
confidence: 99%
“…The copper aversion starvation protocol was adapted from Campbell et al [ 55 ]. Three days before the experiment, animals were synchronized by performing an egg lay on either control or auxin plates.…”
Section: Methodsmentioning
confidence: 99%